Normativni opis in jezikovna standardizacija v aktualnem jezikovnopolitičnem okviru – dokumenti in realnost - Dobrovoljc, Helena (Slavia Centralis, 2020)
Normative description and language standardization in the current language policy framework – resolution and realityIn the article, attention is drawn to the issue of language standardization, namely to one of its phases which must be updated increasingly often – language codifications. Theoretical guidelines are presented and the chronology of the prescriptive activities in Slovenia in the 20th century are shown. The language policy situation is presented in detail, as this area still lacks attention and funding, despite the expressed public interest and the needs of those who write and educate. The situation persists regardless of the binding documents, such as the Resolution on the National Programme for Language Policy 2014–2018 and the Action Plan for Language Infrastructure, which the Ministry of Culture, namely the Slovenian Language Service orders from the experts. They are, however, never realized.
Keywords: language standardization; codification; language policy; normative guide